Label-free biosensing based on single gold nanostars as plasmonic transducers - Dondapati, Srujan K. (2010)
Gold nanostars provide high sensitivity for single nanoparticle label-free biosensing. The nanostars present multiple plasmon resonances of which the lower energy ones, corresponding to the nanostar tips and core-tip interactions, are the most sensitive to environmental changes. Streptavidin molecules are detected upon binding to individual, biotin-modified gold nanostars by spectral shifts in the plasmon resonances. Concentrations as low as 0.1 nM produce a shift of the tip related plasmon resonances of about 2.3 nm (5.3 meV).